Vascular adhesion protein-1 is actively involved in the development of inflammatory lesions in rat models of multiple sclerosis - Elo P; Tadayon S; Liljenback H; Teuho J; Kakela M; Koskensalo K; Saunavaara V; Virta J; Veres TZ; Kiviniemi A; Saraste A; Marjamaki P; et al. (BIOMED CENTRAL LTD, 2022)
Background: Vascular adhesion protein-1 (VAP-1) is an inflammation-inducible endothelial cell molecule and primary amine oxidase that mediates leukocyte entry to sites of inflammation. However, there is limited knowledge of the inflammation-related expression of VAP-1 in the central nervous system (CNS). Therefore, we investigated the expression of VAP-1 within the CNS vasculature in two focal rat models of experimental autoimmune encephalomyelitis (EAE) mimicking multiple sclerosis (MS).Methods: EAE was induced either with Bacillus Calmette-Guerin, resulting in a delayed-type hypersensitivity-like pathogenesis (fDTH-EAE), or with myelin oligodendrocyte glycoprotein (fMOG-EAE). A subgroup of fMOG-EAE rats were treated daily with a selective VAP-1 inhibitor (LJP1586; 5 mg/kg). On 3 and 14 days after lesion activation, rat brains were assessed using magnetic resonance imaging (MRI), and ex vivo autoradiography was conducted to evaluate the binding of Gallium-68-labelled VAP-1 ligand. Histology and immunohistochemistry (OX-42, VAP-1, intercellular adhesion protein-1 [ICAM-1], P-selectin) supported the ex vivo autoradiography.Results: EAE lesions showed MRI-detectable signal changes and binding of the VAP-1-targeting radiotracer in both rat models. Some of the VAP-1 positive vessels showed morphological features typical for high endothelial-like venules at sites of inflammation. Inhibition of VAP-1 activity with small molecule inhibitor, LJP1586, decreased lymphocyte density in the acute inflammatory phase of fMOG-EAE lesions (day 3, P = 0.026 vs. untreated), but not in the remission phase (day 14, P = 0.70 vs. untreated), and had no effect on the amount of OX-42-positive cells in either phase. LJP1586 treatment reduced VAP-1 and ICAM-1 expression in the acute inflammatory phase, whereas P-selectin remained not detectable at all studied stages of the disease.Conclusions: Our results revealed that VAP-1 is expressed and functionally active in vasculature within the induced focal EAE lesions during the acute phase of inflammation and remains expressed after the acute inflammation has subsided. The study indicates that VAP-1 is actively involved in the development of inflammatory CNS lesions. During this process, the endothelial cell lesion-related vasculature seem to undergo a structural transformation from regular flat-walled endothelium to HEV-like endothelium.